Research on the data link layer secure protocol of TES network based on ECC - WU Zhi-jun; KAN Hong-tao (Tongxin xuebao)
A workable and efficient data link layer security protocol had been proposed on the need of safety information transfer requirements of the TES system.The protocol provides a software registration solution for the remote sites and a information encryption method base on the elliptic curves cryptography（ECC） algorithm as well as a combined key allocation method.The protocol takes the characters of the TES system into account,improves its ability to identify remote sites,and provides ways to prevent information stealing and network attacks.